Atorvastatin Reduces the Myocardial Content of Coenzyme Q10 in Isoproterenol-induced Heart Failure in Rats - Andalib, S.; Shayanfar, A.; Khorrami, A.; Maleki-Dijazi, N.; Garjani, A. (Drug Research, 2014)
The present study was aimed to study the effects of different doses of atorvastatin on Co Q10 content in the myocardium tissue in rats. A subcutaneous injection of isoproterenol (5 mg/kg/day) for 10 days was used for the induction of heart failure. Rats were randomly assigned to control, treatment with atorvastatin (5, 10, 20 mg/kg/day) and treatment with atorvastatin plus coenzyme Q10 (10 mg/kg/day). Coenzyme Q10 content of myocardium was measured using HPLC method with UV detector after hemodynamic parameters measurements. The malondialdehyde (MDA) content of the myocardium was evaluated in order to determine coenzyme Q10 antioxidative effect. A high dose of atorvastatin (20 mg/kg/day) was significantly reduced the myocardium content of coenzyme Q10 as compared with isoproterenol treated group (p<0.001). Compared with atorvastatin alone treated animals, co-administration of coenzyme Q10 with atorvastatin was improved the level of coenzyme Q10 in the myocardium (p<0.05, p<0.001). Increasing the dose of atorvastatin also led to increase in MDA content of the myocardium (p<0.01). Serum lipid profile showed no changes in atorvastatin treated groups. The results of this study demonstrate that high doses of atorvastatin reduce coenzyme Q10 content of the myocardium and increase lipid peroxidation in myocardium which is reversed by coenzyme Q10 co-administration.
Keywords: atorvastatin; heart failure; coenzyme Q10; malondialdehyde